Audio Visual Story For Children By Architectural Students "It's Dyra" - Amanda Rosetia; Aprilia Chandrawati; Coral Aswanti; Mikel Owen; Indah Yunita; Elva Christina; Victor Agustian; Deviana Deviana; Rickie Cung (ConCEPt - Conference on Community Engagement Project, 2021)
Since the age of 3, children have been trained to understand the world little by little and shape their own personalities and characters. Children around the age of development tend to learn behavior and articulation through sight and hearing. Hearing educational stories in early ages will help them learn good traits more quickly. Children educative stories can become one of the sources to shape and build good characteristics of children. In collaboration with IOM, HMPS Architecture UIB has created a special audio visual story for children to understand. Delivering story plots with audio and visuals through the story of "It's Dyra" will provide positive results to build positive mindsets of children. The story will be distributed via YouTube and SoundCloud to make it easier to be shared directly to viewers